Effect of Probiotics and Multi-Component Feed Additives on Microbiota, Gut Barrier and Immune Responses in Broiler Chickens During Subclinical Necrotic Enteritis - Emami, Nima K.; Calik, Ali; White, Mallory B.; Kimminau, Emily A.; Dalloul, Rami A. (Frontiers in Veterinary Science, 2020)
The withdrawal of antibiotic growth promoters from poultry feed has increased the risk of necrotic enteritis (NE) outbreaks. This study examined the effects of a probiotic (PROB) or probiotic/prebiotic/essential oil supplement (PPEO) during a subclinical NE challenge. On day (d) of hatch, 960 male broilers were randomized to four groups (8 pens/treatment, 30 birds/pen) including 1) negative control (NC): corn-soybean meal diet; 2) positive control (PC): NC + 20 g Virginiamycin/ton diet; 3) NC + 227 g PROB/ton diet; and 4) NC + 453 g PPEO/ton diet. One day after placement, birds were challenged by a coccidia vaccine to induce NE. Feed intake and body weights were measured on d 8 (NE onset) and end of each feeding period. On d 8, the small intestines of three birds/pen were examined for NE lesions. Jejunum samples and ileal mucosal scrapings from one bird/pen were respectively collected to measure mRNA abundance (d 8 and d 14) and profile the microbiome (d 8 and d 42). Data were analyzed in JMP or QIIME 2 and significance between treatments identified by LSD (P < 0.05). PROB and PPEO had significantly lesser mortality (d 0-14) and NE lesion scores compared to NC. Feed conversion ratio was significantly lesser in PC, PROB and PPEO, while average daily gain was greater in PPEO and PC groups compared to NC from d 0-42. On d 8 and d 14, mRNA abundance of claudin-3 was greater in PPEO compared to NC. On d 14, compared to NC, mRNA abundance of sIgA and PGC-1α in PROB and PPEO were lesser and greater, respectively. Compared to NC, PPEO increased mTOR abundance on d 14. On d 8, relative abundance of Clostridium sensu stricto 1, Ruminiclostridium9, Prevotellaceae, Prevotellaceae UCG-014, ASF356, and Muribaculaceae was greater in NC compared to PPEO and PROB, while Lactobacillus was lesser in NC. Escherichia-Shigella had greater abundance in PC compared to PPEO and PROB. Collectively, these data indicate that during a subclinical naturally occurring NE, supplementation of PROB or PPEO supports performance and reduce intestinal lesions, potentially through modifying TJ proteins, gut microbiome, immune responses, and cell metabolism.